Analysis of traffic accidents in the district Gresik (Case Study: Road Duduksampeyan Sta km 16 + 000 - Sta km 16 + 500) - Debi Fariska; Sri Wiwoho Mudjanarko (IJEEIT : International Journal of Electrical Engineering and Information Technology, 2020)
Traffic accident is an accident that occurs unexpectedly and unintentionally involving a vehicle which resulted in casualties and material damage. The problem of traffic accidents on the road Duduksampeyan Sta km 16 + 000 - Sta km 16 + 500 is the most significant. The purpose of this study was conducted to determine the level of traffic accidents that occurred in 2013-2018. This study uses a method that refers to the calculation of the number of accidents. The observations in the field of road safety facilities are still inadequate, lighting is in only one side of the road as much as ± 10 pieces, and the absence of traffic signs (speed limits, accident-prone areas, etc.). The volume of daily traffic averages on these roads as much as 3833 veh / hour. The results of the analysis carried accident rate by 158 the highest annual accident / km occurred in 2018. Meanwhile, based on the fatality index, it was 47.76%, the highest in 2013.